Pelestarian arsitektur berdasarkan architectural architypes melalui metode grafis - Fransiscus Xaverius Eddy Arinto (ARTEKS : Jurnal Teknik Arsitektur, 2018)
Preservation of cultural heritage is an obligation so that future generations can still enjoy the cultural riches that their predecessor generation has made. In reality, changes occur over time. These changes are sometimes uncontrollable and cause damage to artifacts. They ultimately eliminate the source of discourse and even its characteristics. To maintain cultural sustainability, preservation must be based on the characteristics of the cultural heritage itself. The problem is how to explore and obtain these cultural characteristics so that they can become a foothold in developing further designs. The graphic method for artifacts is one method that helps to explore archetypes, basic characters contained in artifacts in an easier way. This basic character will later become a guideline for the development of a sustainable design. © 2018 Fransiscus Xaverius Eddy Arinto